Old Enemies, Still with Us after All These Years - Clifford, Charles B. (ILAR J, 2008)
Although some previously common infections, such as Sendai virus and Mycoplasma pulmonis, have become rare in laboratory rodents in North American research facilities, others continue to plague researchers and those responsible for providing biomedical scientists with animals free of adventitious disease. Long-recognized agents that remain in research facilities in the 21(st) century include parvoviruses of rats and mice, mouse rotavirus, Theiler's murine encephalomyelitis virus (TMEV), mouse hepatitis virus (MHV), and pinworms. The reasons for their persistence vary with the agent. The resilience of parvoviruses, for example, is due to their resistance to inactivation, their prolonged shedding, and difficulties with detection, especially in C57BL/6 mice. Rotavirus also has marked environmental resistance, but periodic reintroduction into facilities, possibly on bags of feed, bedding, or other supplies or equipment, also seems likely. TMEV is characterized by resistance to inactivation, periodic reintroduction, and relatively long shedding periods. Although MHV remains active in the environment at most a few days, currently prevalent strains are shed in massive quantities and likely transmitted by fomites. Pinworm infestations continue because of prolonged infections, inefficient diagnosis, and the survivability of eggs of some species in the environment. For all of these agents, increases in both interinstitutional shipping and the use of immunodeficient or genetically modified rodents of unknown immune status may contribute to the problem, as might incursions by wild or feral rodents. Elimination of these old enemies will require improved detection, strict adherence to protocols designed to limit the spread of infections, and comprehensive eradication programs.